2015
DOI: 10.1371/journal.pone.0124748
|View full text |Cite
|
Sign up to set email alerts
|

Dried Blood Spots for Viral Load Monitoring in Malawi: Feasible and Effective

Abstract: ObjectivesTo evaluate the feasibility and effectiveness of dried blood spots (DBS) use for viral load (VL) monitoring, describing patient outcomes and programmatic challenges that are relevant for DBS implementation in sub-Saharan Africa.MethodsWe recruited adult antiretroviral therapy (ART) patients from five district hospitals in Malawi. Eligibility reflected anticipated Ministry of Health VL monitoring criteria. Testing was conducted at a central laboratory. Virological failure was defined as >5000 copies/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 45 publications
2
46
0
Order By: Relevance
“…The parent study was a public health evaluation of DBS for VL monitoring at five ART clinics located in district hospitals in central and southern Malawi (Rutstein, et al, 2015). None of the enrolling clinics had access to VL monitoring outside of enrollment in the DBS study; all clinics relied on clinical staging for ART monitoring as CD4-based criteria was not recommended per Malawi guidelines in place during the period of data collection (2013-2014) (“Clinical Management of HIV In Children and Adults,” 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The parent study was a public health evaluation of DBS for VL monitoring at five ART clinics located in district hospitals in central and southern Malawi (Rutstein, et al, 2015). None of the enrolling clinics had access to VL monitoring outside of enrollment in the DBS study; all clinics relied on clinical staging for ART monitoring as CD4-based criteria was not recommended per Malawi guidelines in place during the period of data collection (2013-2014) (“Clinical Management of HIV In Children and Adults,” 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Dried blood spots (DBS) have emerged as an alternative to plasma-based VL testing for resource-limited settings by simplifying specimen collection and storage; centralizing laboratory testing; and reducing the need for extensive clinic-level laboratory infrastructure. DBS collection by ART providers at outlying clinics and a centralized laboratory for specimen testing may increase access to VL monitoring in remote clinics (Johannessen, 2010; Johannessen, Troseid, & Calmy, 2009; Rutstein et al, 2015). The WHO and national ART management guidelines in many resource-limited settings advocate use of DBS as the preferred monitoring model when traditional VL testing is not feasible (“Clinical Management of HIV In Children and Adults,” 2014; WHO, 2013, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification of HIV RNA requires sophisticated facilities and skilled staff and costs have been high, although they have decreased substantially recently (5, 6). While modelling studies have indicated there is a benefit of viral load monitoring over monitoring strategies based on the CD4 count or clinical observation (716) viral load monitoring has not been found to be cost-effective (7, 1014), due to the cost of viral load tests and second-line regimens. Currently, the most feasible approach in most countries to begin to measure viral load is to collect samples as dried blood spots (DBS).…”
Section: Introductionmentioning
confidence: 99%
“…Using existing networks for early infant HIV diagnosis, they can be transported to a regional or national laboratory with results subsequently returned to the clinic by means such as SMS. However, presence of cells and low sample volume in DBS specimens mean that sensitivity and specificity for detecting whether the level is above the 1000 cps/mL threshold used to define viral suppression are imperfect and it is unclear if the approach is adequate (5, 1627). Looking to the future, it is anticipated that “point-of-care” (POC) tests - i.e.…”
Section: Introductionmentioning
confidence: 99%